2013
DOI: 10.1128/jvi.01750-13
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Cytokine/Chemokine Responses in Intestinal CD4+and CD8+T Cells during Acute Simian Immunodeficiency Virus Infection

Abstract: ؉ and CD8 ؉ T cells showed upregulation of macrophage migration inhibition factor (MIF) and basic fibroblast growth factor (FGF-basic) cytokines that have been linked to HIV disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
0
20
1
Order By: Relevance
“…Selective depletion of CD4 ϩ T-cell subsets during chronic MuLV infection induced increased expression of T H 2 cytokines (13). Our study found no evidence of a mucosal T H 1-to-T H 2 or T-cytotoxic 1 (T C 1)-to-T C 2 cytokine profile shift during the acute phase of SIV infection (5). Limited data exist on how cytokine/ chemokine profiles in different T-cell subsets of lymphoid tissues and bone marrow (BM) lymphocytes are affected during the acute phase of HIV infection, despite the fact that peripheral LN and BM are considered major virus reservoirs for HIV/SIV infection (14)(15)(16)(17).…”
Section: H Uman Immunodeficiency Virus Type 1 (Hiv-1) Infection Causecontrasting
confidence: 86%
See 3 more Smart Citations
“…Selective depletion of CD4 ϩ T-cell subsets during chronic MuLV infection induced increased expression of T H 2 cytokines (13). Our study found no evidence of a mucosal T H 1-to-T H 2 or T-cytotoxic 1 (T C 1)-to-T C 2 cytokine profile shift during the acute phase of SIV infection (5). Limited data exist on how cytokine/ chemokine profiles in different T-cell subsets of lymphoid tissues and bone marrow (BM) lymphocytes are affected during the acute phase of HIV infection, despite the fact that peripheral LN and BM are considered major virus reservoirs for HIV/SIV infection (14)(15)(16)(17).…”
Section: H Uman Immunodeficiency Virus Type 1 (Hiv-1) Infection Causecontrasting
confidence: 86%
“…Chronic and deleterious immune activation is a hallmark of HIV/simian immunodeficiency virus (SIV) infection. Our recent data suggest that pathogenic SIV MAC 251 infection induces higher expression of several cytokines/chemokines in plasma, as well as in intestinal single-positive (SP) CD4 ϩ and CD8 ϩ T cells (4,5). Early loss of intestinal CD4…”
Section: H Uman Immunodeficiency Virus Type 1 (Hiv-1) Infection Causementioning
confidence: 99%
See 2 more Smart Citations
“…Epithelial cells and lymphocytes from jejunum and colon were isolated as described earlier (9,(22)(23)(24). Both intraepithelial (IE) and lamina propria (LP) lymphocytes were isolated from intestinal biopsy specimens, resection surgery, or necropsy tissues.…”
Section: Methodsmentioning
confidence: 99%